Critical role of processing on the mechanical properties of cross-linked highly loaded nanocomposites - Suresh, Karthika; Chowdhury, Arindam; Kumar, Sanat K.; Kumaraswamy, Guruswamy (Macromolecules, 2019)
Polymer nanocomposites are frequently not at equilibrium-therefore, the structure and properties critically depend on the protocol followed in their preparation. Here, we demonstrate that the elastic-brittle transition in highly loaded ice-templated polymer nanocomposites is sensitively determined by the conformation of polymer chains during nanocomposite preparation. Macroporous polymer nanocomposites are synthesized using two preparation pathways, both exhibiting minor modifications of the ice-templating method wherein an aqueous dispersion of nanoparticles, polymers, and cross-linkers is frozen. In one method, the matrix polymer is cross-linked in the presence of ice, whereas in the other method, the ice is removed by freeze-drying before the polymer is cross-linked. Although all measurable structural metrics are practically identical for the two composites, they exhibit qualitatively different mechanical properties. Nanocomposites cross-linked in the presence of ice show exceptional resilience, recovering elastically from large compression for very high nanoparticle loadings-in some instances, above 90% by weight. Here, the critical particle loading for the elastic- brittle transition is dependent on the molecular weight of the polymer. In comparison, samples cross-linked after freeze-drying appear structurally identical but turn brittle at much lower particle loadings (about 60% by weight), independent of the matrix polymer molecular weight. We rationalize these differences in terms of the conformational state of the polymer during cross- linking. In the former case, polymer chains are in good solvent during nanocomposite preparation, while after lyophilization, they are in a poor solvent. The large spatial extent of well-solvated chains and chain-chain overlap during cross-linking results in the formation of intermolecular cross-links, and we obtain elastic nanocomposites even at high nanoparticle loadings. In contrast, for chains in collapsed conformations in a bad solvent, chain connectivity during cross-linking is achieved only for much lower particle loadings. Our results reiterate that the sensitivity of polymer conformations to different processing methods can result in large differences in properties, even though their consequences on structural characteristics are effectively indistinguishable.